2017
DOI: 10.1111/1467-8268.12239
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Life Insurance Demand in Tunisia

Abstract: This paper investigates the variables driving the demand for life insurance in Tunisia based on annual macroeconomic data spanning the period from 1990 to 2014 and collected from the Swiss Reinsurance company and the World Bank's databases. We provide a characterization of the Tunisian life insurance sector and a comparison to some emerging markets. Empirical results show that life insurance demand increases with income and financial development. However, other economic variables such as inflation and interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 28 publications
6
59
2
2
Order By: Relevance
“…Concerning the three ICT indicators used this study, the results are broadly consistent with those of Efobi et al (2018) in which, the magnitude of broadband subscriptions on economic development (by means of female economic participation) is substantially higher when compared with internet penetration and mobile phone penetration. The established findings are contrary to Zerriaa et al (2017) who have concluded that the levels education reduces the consumption of life insurance. The main policy implication is that, ICT is valuable in modulating the relevance of education on the subscriptions to life and non-life insurance policies by citizens in Africa.…”
Section: Presentation Of Resultscontrasting
confidence: 83%
See 2 more Smart Citations
“…Concerning the three ICT indicators used this study, the results are broadly consistent with those of Efobi et al (2018) in which, the magnitude of broadband subscriptions on economic development (by means of female economic participation) is substantially higher when compared with internet penetration and mobile phone penetration. The established findings are contrary to Zerriaa et al (2017) who have concluded that the levels education reduces the consumption of life insurance. The main policy implication is that, ICT is valuable in modulating the relevance of education on the subscriptions to life and non-life insurance policies by citizens in Africa.…”
Section: Presentation Of Resultscontrasting
confidence: 83%
“…Third, a great bulk of the literature has focused on two main dimensions, notably: the determinants of life insurance consumption (Guerineau & Sawadogo, 2015;Zerriaa et al, 2017;Alhassan & Biekpe, 2016a) and linkages between insurance penetration and development outcomes (Ioncică et al, 2012;Akinlo, 2015;Alhassan & Biekpe, 2015. The two dimensions are briefly discussed in what follows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs travaux ont analysé la demande des divers biens et services tels que l'assurance (Zerriaa, Amiri, Noubbigh, & Naoui, 2017), les soins médicaux (Anyanwu, 2007), l'éducation (Diagne, 2005; Ogundari & Abdulai, 2014) etc. dans le contexte africain.…”
Section: Revue De La Littératureunclassified
“…Determinants of life insurance have been assessed by Zerriaa et al (2017) using data from 1990-2014. The findings show that interest and inflation rates do not have significant impacts on the dependent variable.…”
Section: Literaure Review On Insurancementioning
confidence: 99%